Differences in Optic Disc Characteristics of Primary Congenital Glaucoma, Juvenile, and Adult Onset Open Angle Glaucoma Patients. Issue 3 (March 2016) - Gupta, Viney; James, Mathew K.; Singh, Anirudh; Kumar, Sandip; Gupta, Shikha; Sharma, Ajay; Sihota, Ramanjit; Kennedy, Dale J.
Abstract : Objective: To comparatively evaluate morphometric features of the optic discs of primary congenital glaucoma (PCG), juvenile onset primary open angle glaucoma (JOAG), and adult onset primary open angle glaucoma (POAG) using scanning laser ophthalmoscopy (HRT3). Methods: Optic discs of previously treated 89 PCG, 136 JOAG, and 139 adult onset POAG patients, were evaluated. One eye of each patient was analyzed in the study. The optic disc characteristics studied included disc area, cup area, rim area, cup depth, cup volume, cup to disc area ratio, horizontal cup to disc ratio, vertical cup to disc ratio, and mean retinal nerve fiber layer (RNFL). A regression analysis was performed to assess the effect of age, sex, and disc area on the disc characteristics in the 3 categories of primary glaucomas. Results: Mean disc area of PCG, JOAG and POAG eyes was 2.58±0.75, 2.61±0.51, and 2.44±0.58 mm 2, respectively. The cup characteristics that demonstrated significantly greater means among JOAG compared with POAG and PCG eyes, included cup depth ( P =0.001), cup volume ( P =0.024), and cup to disc area ratio ( P =0.049). The mean horizontal cup to disc ratio=0.73 was greater than mean vertical cup to disc ratio=0.61 ( P =0.026) among PCG eyes as well as among JOAG eyes ( P =0.001). For POAG, the mean horizontal cup to disc ratio=0.73 was not different from the mean vertical cup to disc ratio=0.69 ( P =0.077). Conclusions: The optic discs of juvenile onset open angle glaucoma tend to be larger in size than adult onset POAG discs. A 3-dimensional enlargement of the cup is seen among treated JOAG discs compared with POAG and PCG eyes. The greater horizontal cup disc ratio in PCG and JOAG compared with POAG eyes indicates a concentric enlargement of the cup in these patients.